Influence of foliar biostimulants based on seaweeds, on the development and yield of rice crops in Daule, Ecuador - González Pita, Alexander de Jesús; Painii Montero, Vicente Frijoth (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
The present research work was carried out in the Limonal parish of the Daule canton, province ofGuayas-Ecuador, during the dry season of 2020. The objective was to evaluate foliar biostimulants from seaweed as a complement to edaphic fertilization to improve agronomics and quality. of grain from the soca rice crop under irrigation; the field experiment was proposed under the Random Block design, four treatments and the same number of repetitions, Duncan’s test at 5% was used to compare means, agronomic and productive variables were evaluated; the Kelpak-based treatment obtained the best result for panicles per m2 , grains per panicle and grain length; Similarly, in the yield variable, it reached the highest average of 7,683 kg/ha; Consequently, it is concluded that the biostimulants were able to improve the productive variables and grain quality.